PERCEPTIONS ON CONTENT LANGUAGE INTEGRATED LEARNING OF STUDENTS AND TEACHERS IN VOCATIONAL SCHOOL - Diah Kurniati; Farid Noor Romadlon (Universitas Muria Kudus, 2021)
The purpose of this study was to determine the attitudes and motivations of students towards the CLIL class and the teacher's perception of the application of CLIL.The research method used is a case study which is included in the qualitative research design based on the type of data collected and analyzed. The participants of the study were 32 students in the eleventh grade of the Multimedia class, one English teacher and one Information Technology (IT) teacher at SMK NU Ma’arif Kudus. The data in this study were collected through questionnaires which were modified from the Attitude/Motivation Test Battery (AMTB). To analyze the data in the form of questionnaires and interview results, the writers referred to the qualitative data analysis technique, which consists of three steps, including reducing the data, displaying the data, as well as conclusion drawing/verifying the data.The result of the study showed that 70% of students argued that CLIL class contributed their learning experience, especially to learn English more in a different setting with additional knowledge about the subject content. Moreover, 18% of them stated that the class changed the setting of learning, and 12 % students thought that the class just focused to the language aspect such as grammar and vocabularies, not the content. It indicated that students had a positive attitude toward CLIL class. Similarly, teachers showed positive perceptions about the implementation of CLIL class because this program encouraged students to participate more in the class and the class activity.